Desulfonylative halogenation of arene sulfonyl chlorides using N-halosuccinimides: Synthesis, molecular docking, and anti-Alzheimer activity. - Yadav, V.; Kumar, R.; Srikrishna, S.; Prasad, V. (Bioorganic & medicinal chemistry letters., 2025)
Considering the significant biological potential of halogenated arenes, we developed a novel and eco-friendly method for accessing dihalogenated arenes viaN-halosuccinimide-promoted desulfonylative halogenation of arenesulfonyl chlorides under metal-free conditions. In silico evaluations of selected compounds for amyloid-beta (A?) protein interactions identified compounds 1d and 2d as promising candidates, exhibiting strong binding potential and low toxicity in wild-type Oregon R flies. Furthermore, these compounds demonstrated significant neuroprotective activity in an A?-induced Alzheimer's disease model in Drosophila, emphasizing the need for further studies in higher organisms and detailed mechanistic investigations.